Video-Assisted Thoracic Surgical Right Upper Lobectomy with Bronchus-First and Simultaneous Vessel Stapling Technique - Zhang, Linyou; Xu, Hao (The Thoracic and Cardiovascular Surgeon, 2018)
A method of video-assisted thoracic surgical (VATS) right upper lobectomy with bronchus-first and simultaneous vessel stapling will be introduced. In this study, all cases underwent two-port VATS as follows: first, the right upper lobe bronchus was identified and stapled; then, all right upper lobe vessels were stapled simultaneously. This method was performed in 50 cases. There was no surgical mortality, hemorrhage, vascular injuries, or conversion. This technique can reduce wound size and operative time and make the operation safer and easier to accomplish.
Keywords: lung cancer treatment; thoracoscopy/VATS; surgery/incisions